Molecular Architecture of the Yeast Nuclear Pore Complex: Localization of Nsp1p Subcomplexes - Fahrenkrog, Birthe (The Rockefeller University Press, 1998)
The nuclear pore complex (NPC), a supramolecular assembly of ∼100 different proteins (nucleoporins), mediates bidirectional transport of molecules between the cytoplasm and the cell nucleus. Extensive structural studies have revealed the three- dimensional (3D) architecture of Xenopus NPCs, and eight of the ∼12 cloned and characterized vertebrate nucleoporins have been localized within the NPC. Thanks to the power of yeast genetics, 30 yeast nucleoporins have recently been cloned and characterized at the molecular level. However, the localization of these nucleoporins within the 3D structure of the NPC has remain elusive, mainly due to limitations of preparing yeast cells for electron microscopy (EM). We have developed a new protocol for preparing yeast cells for EM that yielded structurally well-preserved yeast NPCs. A direct comparison of yeast and Xenopus NPCs revealed that the NPC structure is evolutionarily conserved, although yeast NPCs are 15% smaller in their linear dimensions. With this preparation protocol and yeast strains expressing nucleoporins tagged with protein A, we have localized Nsp1p and its interacting partners Nup49p, Nup57p, Nup82p, and Nic96p by immuno-EM. Accordingly, Nsp1p resides in three distinct subcomplexes which are located at the entry and exit of the central gated channel and at the terminal ring of the nuclear basket.